GLP-1 Suppresses Feeding Behaviors and Modulates Neuronal Electrophysiological Properties in Multiple Brain Regions - Chen, Xin-Yi; Chen, Lei; Yang, Wu; Xie, An-Mu (Frontiers in Molecular Neuroscience, 2021)
The glucagon-like peptide-1 (GLP-1) plays important roles in the regulation of food intake and energy metabolism. Peripheral or central GLP-1 suppresses food intake and reduces body weight. The electrophysiological properties of neurons in the mammalian central nervous system reflect the neuronal excitability and the functional organization of the brain. Recent studies focus on elucidating GLP-1-induced suppression of feeding behaviors and modulation of neuronal electrophysiological properties in several brain regions. Here, we summarize that activation of GLP-1 receptor (GLP-1R) suppresses food intake and induces postsynaptic depolarization of membrane potential and/or presynaptic modulation of glutamatergic or GABAergic neurotransmission in brain nuclei located within the medulla oblongata, pons, mesencephalon, diencephalon, and telencephalon. This review may provide a background to guide future research about the cellular mechanisms of GLP-1-induced feeding inhibition.